2016
DOI: 10.1111/jcmm.12952
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogenes regulate parental gene expression via ceRNA network

Abstract: The concept of competitive endogenous RNA (ceRNA) was first proposed by Salmena and colleagues. Evidence suggests that pseudogene RNAs can act as a ‘sponge’ through competitive binding of common miRNA, releasing or attenuating repression through sequestering miRNAs away from parental mRNA. In theory, ceRNAs refer to all transcripts such as mRNA, tRNA, rRNA, long non‐coding RNA, pseudogene RNA and circular RNA, because all of them may become the targets of miRNA depending on spatiotemporal situation. As binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(161 citation statements)
references
References 70 publications
(84 reference statements)
1
157
0
Order By: Relevance
“…Through luciferase reporter assays, we confirmed that TCONS_00041960 recognized the seed regions of miR‐204‐5p and miR‐125a‐3p. Furthermore, RIP and SPR assays showed that TCONS_00041960 functioned as a sponge of miR‐204‐5p and miR‐125a‐3p, and thus sequesters them from potential mRNAs (An, Furber, & Ji, ). We also found that siRNA against TCONS_00041960 increased miR‐204‐5p and miR‐125a‐3p expression.…”
Section: Discussionmentioning
confidence: 99%
“…Through luciferase reporter assays, we confirmed that TCONS_00041960 recognized the seed regions of miR‐204‐5p and miR‐125a‐3p. Furthermore, RIP and SPR assays showed that TCONS_00041960 functioned as a sponge of miR‐204‐5p and miR‐125a‐3p, and thus sequesters them from potential mRNAs (An, Furber, & Ji, ). We also found that siRNA against TCONS_00041960 increased miR‐204‐5p and miR‐125a‐3p expression.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a non-coding transcript that shares a high degree of homology with a coding gene is likely to share many of its MREs and therefore pseudogenes are good candidates to act as ceRNAs. Indeed, this seems to be the case [13], [47], [48]. Examples of such lncRNAs include a pseudogene homologous to the gene encoding tumour suppressor phosphatase and tensin homologue ( PTEN ), which contains multiple MREs within the 3′UTR shared with the coding gene [48], as well as pseudogenes homologous to the 3′UTRs of the genes encoding tumour suppressor candidate 2 ( TUSC2 ) [49] and forkhead box protein O1 ( FOXO1 ) [50].…”
Section: Functions Of Lncrnamentioning
confidence: 99%
“…To reduce the multiple testing burden, transcripts that may not be of interest can be excluded from the dataset. While pseudogenes or non‐coding RNAs can be informative (An et al , ), they are often ignored in the analysis.…”
Section: Introductionmentioning
confidence: 99%